Vascular endothelial growth factor mediates the therapeutic efficacy of mesenchymal stem cell-derived extracellular vesicles against neonatal hyperoxic lung injury - So Yoon Ahn; Won Soon Park; Young Eun Kim; Dong Kyung Sung; Se In Sung; Jee Yin Ahn; Yun Sil Chang (Experimental and Molecular Medicine, 2018)
Neonatal lung damage: Vesicles as vehicles for treatment Membrane-bound sacs called vesicles, secreted by stem cells, carry a protein that might prevent oxygen damaging the lungs of newborn infants. This damage is particularly prevalent in babies born prematurely. The ‘mesenchymal’ stem cells generate cells of connective tissue, blood and blood vessels. They produce vascular endothelial growth factor (VEGF), a protein known to allow the stem cells to protect against neonatal lung injuries caused by oxygen. In studies with rats, Jee-Yin Ahn, Yun Sil Chang and colleagues at Sungkyunkwan University in South Korea, found secreted vesicles carrying VEGF are as effective as the whole stem cells. They also confirmed that the effect was specifically due to the VEGF. The research extends understanding of the protective action of VEGF and suggests the vesicles should be explored for their therapeutic potential in newborn infants.